Torsade de pointes in an older patient with Takotsubo cardiomyopathy caused by licorice‐induced pseudoaldosteronism: A case report. Issue 7 (19th July 2022) - Yoshida, Chiaki; Yamamoto, Hiroyuki; Inoue, Tomohiro; Itoh, Mitsuaki; Shimane, Akira; Kawai, Hiroya; Takaya, Tomofumi
Abstract: Takotsubo cardiomyopathy (TCM) causes QT interval prolongation, potentially leading to a fatal arrhythmia. We report the first case of TCM associated with licorice‐induced pseudoaldosteronism causing fatal arrhythmia in an older patient on polypharmacy including yokukansan (TJ‐54) and galantamine. Polypharmacy should be resolved to prevent unexpected adverse events in older patients. Abstract : Licorice can cause pseudoaldosteronism, which might be potentially associated with Takotsubo cardiomyopathy (TCM) onset. Furthermore, older patients on polypharmacy who have new onset of TCM might have a potential risk of fatal arrhythmia.